Strategi Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) Melalui Program Mekaar Oleh PT. PNM Kota Medan Perspektif Ekonomi Islam - Fauzi Arif Lubis; Nur Ahmadi Bi Rahmani; Intan Kartika Putri (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to find out how the main priority strategy for empowering micro, small and medium enterprises (MSMEs) through Mekaar PT.Pnm Medan City is by presenting the internal and external conditions that have been carried out so far. Then in addition, the researcher also explained some of the urgency of handling that needs to be implemented so that the empowerment of SMEs can be more focused. The method used is a qualitative method using SWOT analysis and QSPM. The number of respondents who filled out the questionnaire was 5 respondents from MSME actors and 5 respondents from experts. Based on the results of the SWOT analysis, the strategy quadrants obtained after being processed in the IFE and EFE matrices are in Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy means that the company has strengths and opportunities. Furthermore, in the QSPM analysis, the results show that the main priority strategy that must be carried out is to maintain a harmonious relationship between customers and Mekaar PT.PNM employees in order to generate positive benefits for the customer's business.